Lifestyle Behaviors and Burnout in Undergraduate Nursing Students: A National Cross-Sectional Study - Danielle J. Durant; Claudia Guerrazzi-Young; Normajean Colby; Faith Chapman; Jonah S. Dunn (Nursing Education Perspectives, 2026)
BACKGROUND Burnout, characterized by exhaustion, cynicism, and low professional efficacy, is the primary cause of nurse turnover. Healthy behaviors, which vary by geographic region, may reduce burnout. METHOD Undergraduate nursing students in Northern ( n = 257) and Southern ( n = 261) programs were surveyed. Multivariate linear regression and dominance analyses were conducted. RESULTS Expression of burnout did not differ across regions. Social support, associated with reduced cynicism ( p = .006) and greater efficacy ( p < .001), was the highest-ranking predictor of exhaustion, cynicism, and efficacy. Physical activity was associated with reduced exhaustion ( p = .027). Healthy diet ( p = .035) and regular spiritual practice ( p = .044) were associated with increased efficacy. CONCLUSION Physical activity, social support, a healthy diet, and spiritual practice may prevent burnout in nursing students. Programs that build healthy habits in students may reduce their experience of burnout.